Inversión extranjera directa y crecimiento económico en Colombia y México: Un análisis comparativo a través de series de tiempo con mínimos cuadrados generalizados (1994-2017); Foreign direct investment and economic growth in Colombia and Mexico: A comparative analysis through time series with generalized least squares (1994-2017) - Edison Javier Jiménez López; Alejandro Mungaray; Benjamín Burgos Flores (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2025)
– A considerable increase in the flows of Foreign Direct Investment (FDI) in Latin America has been observed in recent years, especially in Colombia and Mexico. Using the time series methodology with generalized least squares, this work aims to analyze the impact of FDI and its spillover effects on the economic growth of the two countries. In this way, it is found that in the case of Mexico the direct effects that FDI leaves on its economy are positive; however, in the case of Colombia these effects are negative. Finally, the obtained results show that the spillover effects on economic growth, measured as an indirect effect, produce a positive impact on both countries.
Keywords: C22; F21; O30; O40; O47; 330; Foreign investment; economic growth; time; series model; Latin America; Mexico; Colombia